Climate policy and corporate behaviour - Nicola Commins; Seán Lyons; Marc Schiffbauer; Richard S.J. Tol (The Economic and Social Research Institute (ESRI), 2009)
In this paper, we study the impact of energy taxes and the EU ETS on a large number of firms in Europe between 1996 and 2007. Using company level micro-data, we examine how firms in different sectors were affected by environmental policies. Aspects of behaviour and performance studied include total factor productivity, employment levels, investment behaviour and profitability. On the whole, energy taxes increased total factor productivity and returns to capital but decreased employment, with a mixed effect on investment, for the sectors included in our analysis. However, large sectoral variation is observed, with some industries losing out in terms of productivity and profitability when faced with increased energy taxes, while others benefitted.
Keywords: 330; energy taxes; productivity; investment; firm performance; Umweltpolitik; Ökosteuer; Emissionshandel; Wirkungsanalyse; Produktivität; Betriebliche Investitionspolitik; Beschäftigung; EU-Staaten